The Effect of Phacoemulsification on Corneal Endothelial Cells Morphology and Thickness: Doi:10.36351/pjo.v36i4.1092 - Elmadina, Abd Elaziz Mohamed; Abdelfatah, Raghda Faisal; Alrasheed, Saif Hassan; Abdu, Mustafa; Qureshi, Manzoor Ahmad (Pakistan Journal of Ophthalmology, 2020)
Purpose: To compare the corneal endothelial cells morphology and central corneal thickness (CCT) before and after phacoemulsification in Sudanese population. Place and Duration of Study: Al-Neelain eye hospital, Khartoum, Sudan, from January 2018 to May 2018. Study Design: Observational longitudinal study. Methods: One hundred and forty eyes of 140 patients with immature senile cataract were selected by convenient sampling. The age ranged from 40 to 85 years. The patients underwent complete ocular examination including morphology of corneal endothelial cells and CCT using computerized non-contact specular microscope. Inclusion criteria for the study was eyes with normal corneal endothelial cells and cell density more than 1000 cells/mm2. We excluded patients with ocular or systemic diseases, previous history of intraocular surgery, refractive surgery or trauma as well as contact lenses wear. The patients underwent phacoemulsification by a single surgeon. The examination parameters were repeated one month after surgery. Descriptive and comparative statistical analyses were performed using SPSS for Windows Version 21.0. Results: There was significant reduction in mean endothelial cells density after phacoemulsification compared to baseline with p < 0.001. There was also significant post-operative reduction in mean endothelial cells number as compared to baseline (P value < 0.001). Mean endothelial cells hexagonality was reduced after surgery with P value of 0.003. No significant difference was found between mean coefficient variation of endothelial cells size before and after phacoemulsification (P = 0.55). Central corneal thickness showed significant increase post-operatively, P = 0.003. Conclusion: Phacoemulsification causes significant damage to corneal endothelium cells, including decrease in corneal endothelial cell density, hexagonality and cell number. Key Words: Corneal endothelium, Endothelial cell density, Central corneal thickness, Phacoemulsification.